Common PTP4A1‐PHF3‐EYS variants are specific for alcohol dependence. (13th September 2013) - Zuo, Lingjun; Wang, Kesheng; Wang, Guilin; Pan, Xinghua; Zhang, Xiangyang; Zhang, Heping; Luo, Xingguang
<x xml:space="preserve">Abstract</x> Background and Objectives We previously reported a risk genomic region (ie, PTP4A1‐PHF3‐EYS) for alcohol dependence in a genome‐wide association study (GWAS). We also reported a rare variant constellation across this region that was significantly associated with alcohol dependence. In the present study, we significantly increased the marker density within this region and examined the specificity of the associations of common variants for alcohol dependence. Methods One African‐American discovery sample (681 cases with alcohol dependence and 508 controls), one European‐American replication sample (1, 409 alcohol dependent cases and 1, 518 controls), and one European‐Australian replication sample (a total of 6, 438 family subjects with 1, 645 alcohol dependent probands) underwent association analysis. A total of 38, 714 subjects from 18 other cohorts with 10 different neuropsychiatric disorders served as contrast groups. Results We found 289 SNPs that were nominally associated with alcohol dependence in the discovery sample (p < .05). Fifty‐six associations of them were significant after correction (1.9 × 10−6 ≤ p ≤ 1.6 × 10−5). No markers were significantly associated with other neuropsychiatric disorders after experiment‐wide correction. Conclusions and Scientific Significance We confirmed with our previous findings that PTP4A1‐PHF3‐EYS variants were significantly associated with alcohol dependence, which were replicable across multiple independent populations and were specific for alcohol dependence. These findings suggested that this region might harbor a causal variant(s) for alcohol dependence. (Am J Addict 2014;23:411–414)